Analisis dan Desain Stabilitas Lereng pada Jembatan Pango Menggunakan Software Rocscience Slide 6.0 - Al-Fahrozy Siregar, Syahreza; Syahputra, Ichsan; Silviana, Mery (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
The Pango Bridge is a construction structure whose function is as an important sector in the city of Banda Aceh in connecting traffic routes on the Medan - Banda Aceh road section. The bridge, which was built in 2010, is 200 m long and 45 m wide, leading to Jalan Prof. Ali Hasjmi, making it easier for people to access the BPKP Ulee Kareng intersection. With a fairly high bridge design, the Pango Bridge has two openings on the side of the bridge that lead to Jalan Prof. Ali Hasjmi as an uphill route and another route leading to the Medan – Banda Aceh road as a downhill route. Observations in the field found that the oprit on the 70.2 m uphill route found several damages along with cracks in the existing retaining walls, thus raising suspicions about the safety factor of the Pango bridge oprit slope. This research aims to analyze slope stability as a preventive measure against the possibility of landslides due to unstable slopes. In this research the analysis was carried out using assistance Software Rocscience Slide 6.0. Software Rocscience Slide 6.0 is a computer program that can model slopes using the method balance limit and will automatically display calculations of safety factor values ​​as well as a depiction of the slip plane of a slope. In analyzing a slope, data on the height, width and slope of the slope is needed. Soil parameter data in the form of soil unit weight (γ), shear angle (ϕ), as well as the soil cohesion value (c) is also required because it affects the slip style of a slope. An effort so that the stability analysis has the value of comparative results, then the method is chosen Bishop Simplified as an alternative calculation result value. In the initial analysis the results of the method were good Rocscience as well as methods Bishop Simplified The safety factor value is <1.25, which means that the slope of the Pango bridge is unstable and has the potential for landslides. Application Soil Nailing was also carried out as a step to increase the stability value of the slope. After several experiments, the stability value results were obtained section 1 with method Rocscience were 1,926 > 1.25 and 2,176 > 1.25 by method Bishop. Results on section 2 by method Rocscience is 1,362 > 1.25 and 1,670 > 1.25 by method Bishop. Then finally the results are on section 3 by method Rocscience were 1,516 >1.25 and 1,983 >1.25 by method Bishop. These three results explain that the stability value has been able to exceed the permit safety factor, which means that the slopes of the Pango bridge are safe from landslides when installed. Soil Nailing applied to slopes.